Teori Tabula Rasa dan Teori Konvergensi terhadap Perkembangan Anak di Indonesia: Systematic Literature Review - Serma Adi, Ni Nyoman; I Wayan Suastra; Ananta Wikrama Tungga Atmaja; I Nyoman Tika (SENTRI: Jurnal Riset Ilmiah, 2025)
The purpose of this study is to find and analyze literature discussing the influence of the Tabula Rasa theory and the Convergence theory on child development. Scientific articles published between 2020 and 2025 indexed by SINTA and Scopus were reviewed using a Systematic Literature Review (SLR) approach. The analysis results show that the Tabula Rasa theory, rooted in John Locke's empirical perspective, emphasizes the importance of children's experiences and environment in building their character and abilities. However, the convergence theory created by William Stern combines innate factors (heredity) and environmental factors (environment) as interconnected components in shaping child development. Studies show that the convergence approach is considered more appropriate to the complexity of child development in the digital era. Consequently, most recent studies use this approach as the basis for modern educational models. According to this study, the integration of these two theories remains relevant for pedagogical approaches and curriculum development in the 21st century.